2017
DOI: 10.1038/ncb3615
|View full text |Cite
|
Sign up to set email alerts
|

miR-25/93 mediates hypoxia-induced immunosuppression by repressing cGAS

Abstract: The mechanisms by which hypoxic tumors evade immunological pressure and anti-tumor immunity remain elusive. Here, we report that two hypoxia-responsive microRNAs, miR25 and miR93, are important for establishing an immunosuppressive tumor microenvironment by down-regulating expression of the DNA-sensor cGAS. Mechanistically, miR25/93 targets NCOA3, an epigenetic factor that maintains basal levels of cGAS expression, leading to repression of cGAS upon hypoxia. This allows hypoxic tumor cells to escape immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 46 publications
2
99
0
2
Order By: Relevance
“…Recently, cGAS and STING were identified as intracellular sensors that activate the interferon pathway and mediate host defense; this role might be influenced by miRNAs [12,32,49]. Wu showed that miR25/93 mediates hypoxia-induced immunosuppression by repressing cGAS [51], and Huang revealed that miR-24 regulates STING in rats [15]. Similarly, our results showed that miR-378b could bind TBKBP1 and increase the expression of TBK1 to activate the cGAS/STING pathway.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, cGAS and STING were identified as intracellular sensors that activate the interferon pathway and mediate host defense; this role might be influenced by miRNAs [12,32,49]. Wu showed that miR25/93 mediates hypoxia-induced immunosuppression by repressing cGAS [51], and Huang revealed that miR-24 regulates STING in rats [15]. Similarly, our results showed that miR-378b could bind TBKBP1 and increase the expression of TBK1 to activate the cGAS/STING pathway.…”
Section: Discussionsupporting
confidence: 58%
“…We further verified that ZNF205‐AS1 increased EGR4 mRNA stability, and therefore up‐regulated EGR4 expression. microRNAs (miRNAs) are well‐known to bind the 3’UTR of target mRNAs and induce the degradation and/or translation inhibition of target mRNAs . The interaction between ZNF205‐AS1 transcript and EGR4 mRNA 3’UTR may protect EGR4 mRNA from miRNAs‐induced degradation, which need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[105][106][107][108][109][110] Accordingly, RCD can no longer be perceived as immunogenic when: (1) the intracellular stress responses regulating the emission of ICD-associated DAMPs are pharmacologically or genetically ablated in cancer cells; or (2) when the molecular machinery dedicated to DAMP detection is inhibited or ablated. 13,44,84,91,93,97 Moreover, ICD-driven immunity can no longer operate in the presence of general immunological defects, 111 such as (1) an intrinsically low antigenicity of cancer cells, owing to low levels of TAAs or downregulation of MHC Class I molecules [112][113][114][115][116][117][118][119] ; (2) an increased immunological tolerance of the host, secondary to increased amounts of immunosuppressive cytokines, [120][121][122][123][124][125][126][127][128] or inhibitors of chemotaxis, [129][130][131][132][133][134] increased tumor infiltration by immunosuppressive cell populations, [135][136][137][138][139][140]…”
Section: Introductionmentioning
confidence: 99%